Judy Moody and the not bummer summer - Beatty, Jordana, 1998-; Graham, Heather, 1970-; Mosteller, Parris; Bailey, Preston, 2000-; Ryan, Garrett; Hender, Taylar; Winters, Kristoffer; Varney, Janet, 1976-; White, Jaleel, 1976-; Siegel-Magness, Sarah; Magness, Gary.; Waugh, Kathy; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2011)
Feisty, fearless Judy Moody is looking forward to the most super-duper, double-rare summer vacation ever. The trouble is, her parents are called out of town and her BFFs are going away with their own families. That leaves Judy trapped at home with her pesky brother Stink under the watchful eye of Aunt Opal. But with a little playful planning, and a lot of imagination, Judy turns a snoresville summer into the way-not-boring adventure of a lifetime!
Title from container.
Based on the "Judy Moody" book series by Megan McDonald.
Bonus features: join the Toad-Pee Club ; Flippin' out with the cast ; Camryn's "Wait and see" music video ; 10 things you need to know about Judy Moody ; Judy Moody's guide to making a movie ; deleted scenes ; theatrical trailer.
Director of photography, Shawn Maurer ; film editor, John Pace III ; music by Richard Gibbs.
Jordana Beatty, Heather Graham, Parris Mosteller, Preston Bailey, Garrett Ryan, Taylar Hender, Kristoffer Winters, Janet Varney, Jaleel White.
MPAA rating: PG; for some mild rude humor and language.
Keywords: Moody, Judy (Fictitious character) -- Juvenile films; Moody, Judy (Fictitious character) -- Drama; Feature films; Children's films; Fiction films; Video recordings for the hearing impaired; Feature films; Comedy films